Two new species of Aegopsis Burmeister, 1847 (Coleoptera: Scarabaeidae: Dynastinae) from the central Brazilian Cerrado - Sobral, Rafael; Grossi, Paschoal C.; de Morais, José W. (Zootaxa, 2018)
Two new species of Aegopsis Burmeister, 1847 (Coleoptera: Scarabaeidae: Dynastinae: Agaocephalini), Aegopsis diceratops Sobral & Grossi new species and Aegopsis vazdemelloi Sobral & Grossi new species, are described and illustrated based on specimens collected in Cerrado habitat in the Brazilian states of Minas Gerais and Mato Grosso. The new species are similar to A. bolboceridus (Thomson, 1860). A redescription of A. bolboceridus is provided along with remarks comparing characters among these three species. A distribution map and a male and female key to the species in the genus are provided.